The Role of GFAP as a Marker of Astrocyte Activation in the Pathogenesis of Alzheimer's Dementia: A Literature Review - Trisna Sumadewi, Komang (Indonesian Journal Publisher, 2025)
This study aims to comprehensively review the role of glial fibrillary acidic protein (GFAP) as a marker of astrocyte activation in Alzheimer's disease (AD). The research utilized a descriptive-qualitative literature review approach by analyzing various current scientific sources, including indexed international journal articles, research reports, and relevant academic documents published between 2015 and 2025. Data collection involved systematic literature search techniques, followed by analysis comprising theme identification, data reduction, concept categorization, and inductive conclusion drawing to obtain a holistic understanding of the phenomenon under study. The study results show that GFAP plays a crucial role as a sensitive biomarker for astrocyte activation that occurs since the preclinical phase of Alzheimer's, demonstrating a strong correlation with amyloid-beta accumulation and the neuroinflammatory process. In addition to its function in early detection, GFAP is also capable of predicting the conversion of mild cognitive impairment (MCI) to Alzheimer's dementia with high diagnostic accuracy. Despite limitations in specificity and measurement variation, the integration of GFAP with other biomarkers such as pTau, NfL, and YKL-40 significantly enhances diagnostic validity and its potential for therapy monitoring. In conclusion, GFAP is a multifunctional biomarker that not only deepens our understanding of the mechanisms of reactive astrocytosis in AD pathogenesis but also provides new directions for the development of non-invasive diagnostics and more precise therapeutic strategies in neurodegenerative diseases.